REFLEKSI BUDAYA JAWA DALAM NOVEL BUMI MANUSIA DAN ANAK SEMUA BANGSA KARYA PRAMOEDYA ANANTA TOER: PERSFEKTIF FILSAFAT - Erfi Firmansyah (Faculty of Humanities, Jember University, 2013)
The philosophy of science in the Javanese philosophy is limited in number. Therefore, Pramoedya criticizes the lack of contribution of the Javanese culture and people to modern science. Bumi Manusia and Anak Semua Bangsa form an autocriticism to the Javanese philosophy that should become a guide to thought and action. Both novels invite the readers to criticize the Javanese philosophy, its strenghts and weaknesses. The study to the novels reveals that the Javanese philosophy is a philosophy of values, especially ethics. This issue is deeply and broadly elaborated in terms of its truth and effectivity in conncetion with the Indonesian nation’s progress in particular and the world in general. Keywords: autocritics, culture, philosophy, values, and science